2006
DOI: 10.1038/nbt1177
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of human embryonic stem cells in defined conditions

Abstract: We have previously reported that high concentrations of basic fibroblast growth factor (bFGF) support feeder-independent growth of human embryonic stem (ES) cells, but those conditions included poorly defined serum and matrix components. Here we report feeder-independent human ES cell culture that includes protein components solely derived from recombinant sources or purified from human material. We describe the derivation of two new human ES cell lines in these defined culture conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
818
1
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,015 publications
(844 citation statements)
references
References 15 publications
15
818
1
10
Order By: Relevance
“…These cells initially were cultivated on a layer of feeder cells in a serum‐ or KSR‐supplemented medium,104 but in anticipation of clinical applications, the efforts shifted to the development of culture conditions that are feeder‐free and xeno‐free (Table 5). 105, 106, 107, 108, 109, 110, 111 Among these, the E8 medium that was developed by Guokai Chen et al. has become popular.…”
Section: History Of Cell Culture Mediamentioning
confidence: 99%
“…These cells initially were cultivated on a layer of feeder cells in a serum‐ or KSR‐supplemented medium,104 but in anticipation of clinical applications, the efforts shifted to the development of culture conditions that are feeder‐free and xeno‐free (Table 5). 105, 106, 107, 108, 109, 110, 111 Among these, the E8 medium that was developed by Guokai Chen et al. has become popular.…”
Section: History Of Cell Culture Mediamentioning
confidence: 99%
“…However, viral contamination of feeder cells is a common risk in all biotechnological products derived from cell lines, irrespective of the species of origin [22]. For future experiments, we want to carry out the culture of ECSs in a serum-free system in order to eliminate dependence on the culture and the inactivation of murine fibroblasts as well as the risk of contamination with animal pathogens [23].…”
Section: Discussionmentioning
confidence: 99%
“…The major constituents of Matrigel are laminin, collagen, and heparan sulphate proteoglycans. Subsequently, various matrices, including laminin (Beattie et al, 2005), fibronectin (Amit et al, 2004) and vitronectin (Braam et al, 2008), and combinations of laminin, fibronectin, and collagen IV with (Ludwig et al, 2006) or without vitronectin (Draper et al, 2004), were reported to support hESC propagation in different media. Most of these ECM proteins are abundant in the human placenta.…”
Section: Hipscs Have Multi-lineage Differentiation Potentialsmentioning
confidence: 99%
“…Nuclei were stained with DAPI (Sigma). FACS analysis was performed as described (Ludwig et al, 2006).…”
Section: Generation Of Hipscsmentioning
confidence: 99%